Electrochemical Fabrication and Characterization of Palladium Nanowires in Nanoporous Alumina Templates. Issue 12 (7th September 2020) - Larsson, Alfred; Abbondanza, Giuseppe; Linpé, Weronica; Carlà, Franceso; Mousley, Philip; Hetherington, Crispin; Lundgren, Edvin; Harlow, Gary S.
Abstract : A method for the electrochemical synthesis of palladium nanowires, using porous alumina templates with diameters of 25 nm and 40 nm, is presented. Through an electrochemical barrier layer thinning step, pulsed electrodeposition can take place directly into the anodized aluminum; without need for extra removal, pore opening, and metal contact coating steps. A digital oscilloscope is used to record and integrate the current, allowing the efficiency of the electrodeposition to be calculated. We discuss how using a large "off period" allows for the replenishment of the depleted diffusion layer. The nanowires are characterized by using a focused ion beam (FIB) to create cross-sections which can be accessed with a scanning electron microscope (SEM). With grazing-incidence X-ray diffraction (GI-XRD) we find that the nanowires have a slight compressive strain in the direction that they are confined by the pores (0.58% and 0.51% for the 25 nm and 40 nm pores respectively). Knowing the strain state of the nanowires inside the template is of importance for the use of templated nanowires in devices. Further characterization is made using high-resolution transmission electron microscopy (HR-TEM) and energy dispersive X-ray spectroscopy (EDS), after removal from the alumina templates.